SUSTITUCIÓN DE LA MÁXIMA AUTORIDAD DE ELECCIÓN UNIPERSONAL IMPOSIBILITADA DE POSESIONARSE EN EL CARGO - Chaunay Guanca, Katty Margoth (2016)
This legal research, framed in the field of constitutional law, whose theme is: "REPLACING THE ADMINISTRATIVE AUTHORITY MAXIMUM CHOICE UNIPERSONAL prevented from taking office in" the same as it is aimed at carrying out a case study of the canton Muisne -province of Esmeraldas and a discussion of constitutional and legal provisions that directly affect the subrogation of the former authority of the autonomous governments that do not directly elect the second authority, but is chosen from among those who make up the body school respective. That is why we do a thorough analysis of the rules contained in the Organic Electoral Code of Democracy and the Organic Code of Territorial Organization, Autonomy and Decentralization Law related to the election of the second authority of the autonomous government decentralized call to replace in case of permanent absence of the first authority The Constitution provides for the democratic principle and the proportional electoral system for multi-person elections. The electoral law, Code of democracy and COOTAD not regulate cases of permanent absence of the highest administrative authority when their disability to exercise the office occurs after his election and before his inauguration. Under this assumption, the state, the actions of the State as ultimate guarantor of rights in Ecuador, should be subject to the Constitution of the Republic and directly applying the rights recognized therein.